Effects of aerobic physical exercise on neuroplasticity after stroke: systematic review - Penna, Leandro Goursand; Pinheiro, João Pascoa; Ramalho, Sergio Henrique Rodolpho; Ribeiro, Carlos Fontes (Arquivos de Neuro-Psiquiatria, 2021)
Background: Stroke is among the leading causes of death and disability worldwide. Interventions for stroke rehabilitation aim to minimize sequelae, promote individuals’ independence and potentially recover functional damage. The role of aerobic exercise as a facilitator of post-stroke neuroplasticity in humans is still questionable. Objective: To investigate the impact of aerobic exercise on neuroplasticity in patients with stroke sequelae. Methods: A systematic review of randomized clinical trials and crossover studies was performed, with searches for human studies in the following databases: PUBMED, EMBASE, LILACS and PeDRO, only in English, following the PRISMA protocol. The keywords used for selecting articles were defined based on the PICO strategy. Results: This systematic review evaluated the impacts of aerobic exercise on neuroplasticity through assessment of neural networks and neuronal excitability, neurotrophic factors, or cognitive and functional assessment. Studies that evaluated the effects of aerobic exercise on neuroplasticity after stroke measured through functional resonance (fMRI) or cortical excitability have shown divergent results, but aerobic exercise potentially can modify the neural network, as measured through fMRI. Additionally, aerobic exercise combined with cognitive training improves certain cognitive domains linked to motor learning. Studies that involved analysis of neurotrophic factors to assess neuroplasticity had conflicting results. Conclusions: Physical exercise is a therapeutic intervention in rehabilitation programs that, beyond the known benefits relating to physical conditioning, functionality, mood and cardiovascular health, may also potentiate the neuroplasticity process. Neuroplasticity responses seem more robust in moderate to high-intensity exercise training programs, but dose-response heterogeneity and non-uniform neuroplasticity assessments limit generalizability.
Keywords: Stroke; Stroke Rehabilitation; Exercise; Neuronal Plasticity; Endurance Training; High-Intensity Interval Training; Brain-Derived Neurotrophic Factor; Nerve Growth Factor